Terra Tiles Sdn Bhd / Zuriana Mohd Rasidi ... [et.al] - Mohd Rasidi, Zuriana; Md. Fadzil, Siti Khadijah; Arith, Zulfa; Zaki, Zaidi; Zainal Abidin, Noraihan (Faculty of Civil Engineering, 2004)
The stories of Bumiputera entrepreneurs in the trading tiles industry are disagreeable and unpleasant and sometimes dishearten enough, but still few of them emerges and succeeds in the industry. We would like to increase the numbers of Bumiputera in the industry and we would like to at least motivate them to open the business. As a leader in the tiles industry, we would like to raise the benchmark further. We would also like to provide an excellence in quality of service and the products that we sell, The products that we want to sell are categorized depends on the design and the finishing of the tiles. Generally, there are three types of ranging from fully-vitrified homogenous glazed tiles, glazed ceramic wall and floor tiles and special decorative border tiles of various shapes and sizes. The products that we might sell are locally produced such as White Horse and Guocera as these two brands emerge as the main names in the construction industry. Middle class people, design company or someone related to the construction industry are our main target market. They have the power to choose the design that they required and most of them seek good quality tile products. Our company will provider a varying tiles which suits with all the needs of the customers according to the design, texture and the sizes. By selling a good quality products, we would like to satisfy our customers so that they will not only know the quality tiles that we sell, but we also would like to provide a good services to them.